COLLABORATIVE MITIGATION STRATEGIES AND SUPPLY CHAIN RISK MANAGEMENT: INFORMATION PROCESSING THEORY PERSPECTIVE - Saglam, Yesim Can; Sezen, Bülent; Cankaya, Sibel Yildiz (Future Acad, 2019)
Although recently there has been great interest in supply chain risk management (SCRM), little is known about in the field of risk management why some supply chains perform well, whereas others do not. For this reason, this study focuses on variables that can improve SCRM performance. Collaborative risk mitigation strategies, namely, risk information sharing, decision synchronization, goal congruence, resource sharing, and collaborative communication have been rarely theoretically analyzed in relation to SCRM performance by considering the moderating effect on relational risk in the field of SCRM literature. Therefore, to enhance information processing theory (IPT), the purpose of this study is to investigate the effect of collaborative risk mitigation strategies on SCRM performance with considering the effect of relational risk. This study develops a conceptual model encapsulating interrelationships between collaborative risk mitigation strategies and SCRM. By using IPT, this paper investigates how collaborative risk mitigation strategies can influence SCRM performance by considering the moderator effect of relational risk. Findings of this study propose that (1) collaborative risk mitigation strategies are positively related to SCRM performance (2) relational risk moderates the relationships between collaborative risk mitigation strategies and SCRM performance. This paper renders contribution to SCRM literature by presenting a model of interrelationships among collaborative risk mitigation strategies and SCRM performance. (C) 2019 Published by Future Academy www.FutureAcademy.org.uk
15th International Strategic Management Conference (ISMC) -- JUN 27-29, 2019 -- Poznan, POLAND
Keywords: Supply chain risk management; mitigation strategy; relational risk; information processing theory